Stress reduction of diamond-like carbon by Si incorporation: A molecular dynamics study - Li, Xiao-Wei; Joe, Min-Woong; Wang, Ai-Ying; Lee, Kwang-Ryeol (ELSEVIER SCIENCE SA, 2013)
The residual stress and atomic bond structure of Si-incorporated diamond-like carbon films were investigated by the molecular dynamics simulation using Tersoff interatomic potential. The effect of Si incorporation into amorphous carbon matrix was analyzed for the various Si concentrations ranging from 0 to 2.1 at.%. The present simulation revealed that the incorporation of a small amount of Si significantly reduced the residual compressive stress: when the Si content was 0.54 at.%, the minimal compressive stress of 1.4 GPa was observed. Structural analysis using the radial distribution function and the bond angle distribution indicated that the compressive stress reduction resulted from the relaxation of highly distorted bond angles less than 109.5 degrees. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: TETRAHEDRAL AMORPHOUS-CARBON; TRIBOLOGICAL PROPERTIES; STRUCTURAL-PROPERTIES; DLC COATINGS; THIN-FILMS; DEPOSITION; GROWTH; MODEL; SIMULATIONS; ENERGY